2017
DOI: 10.15835/nsb9210002
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Yield Attributes Responses of Soybean (Glycine max L. Merrill) to Elevated CO2 and Arbuscular Mycorrhizal Fungi Inoculation in the Humid Transitory Rainforest

Abstract: Variations in yield components and grain yield of arbuscular mycorrhizal fungi (AMF) inoculated soybean varieties (Glycine max L. Merrill) grown in CO 2 enriched environment in the humid rainforest were tested. A screen house trial was established with soybean varieties ('TGx 1448-2E', 'TGx 1440-1E' and 'TGx 1740-2F'), AMF inoculation (with and without) and CO 2 enrichment (350±50 ppm and 550±50 ppm) in open top chamber, arranged in completely randomised design, replicated three times. A field trial was also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
(37 reference statements)
2
6
0
Order By: Relevance
“…The present study also revealed increased seed yield and yield attributes of the soybean cultivars under elevated CO 2 . The result was in consistent with previous reports (Sakariyawo et al, 2016;Adeyemi et al, 2017). This positive response could be attributed to enhance net photosynthesis and dry matter accumulation prior to the formation of the yield attributes, resulting in improve seed yield.…”
Section: Effects Of Elevated Co 2 On Plant Biomass and Yield Componensupporting
confidence: 93%
See 1 more Smart Citation
“…The present study also revealed increased seed yield and yield attributes of the soybean cultivars under elevated CO 2 . The result was in consistent with previous reports (Sakariyawo et al, 2016;Adeyemi et al, 2017). This positive response could be attributed to enhance net photosynthesis and dry matter accumulation prior to the formation of the yield attributes, resulting in improve seed yield.…”
Section: Effects Of Elevated Co 2 On Plant Biomass and Yield Componensupporting
confidence: 93%
“…Being a C 3 plant and a crop with high phosphorus (P) demand may be more sensitive to elevated CO 2 compared to other non-leguminous crops (Rogers et al, 2006). Soybean is reported to respond positively to elevated CO 2 with higher productivity (Ziska and Bunce, 2000;Sakariyawo et al, 2016;Adeyemi et al, 2017). Previous researchers have focused their studies on above ground changes in response to elevated CO 2 , but recently some of the findings revealed that elevated CO 2 could also influence below ground microbial properties, which in turn affects plant productivity (Bhattacharyya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The increased soil availability and content of N and P might have also favoured leaf area expansion needed for light interception during photosynthesis (Pablo-Barbieri et al, 2008;Otie et al, 2019). The N and P is also essential for yield formation because of their essential role in plant metabolic processes and assimilate partitioning (Akmal et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Like in our previous study (Ranjbar Sistani et al, 2017), which focused on effects of bacterial (Rhizobium) symbiosis on pea seeds, here, we found that AMF had a significant impact on seed yield, seed (FW and DW) per seed, TSW (FW and DW), seed (FW) per plant, pod weight, and pod size. In earlier studies, the notable influence of AMF root colonization on seed yield enhancement (Cely et al, 2016;Adeyemi et al, 2017), seed weight per plant (Abdel-Fattah et al, 2016), pod weight (Abdel-Fattah et al, 2016;Adeyemi et al, 2017), and hundredseeds weight (Kavitha and Nelson, 2014;Abdel-Fattah et al, 2016) has been observed. Specific proteins such as glutamine synthetase (N-metabolism), enolase (glycolysis), the protein disulfide isomerase (redox), malate dehydrogenase (TCA cycle), peptidyl-prolyl cis-trans isomerase (cell) were remarkably enhanced in seed proteome of M vs. NM pea plants.…”
Section: Positive Effects Of Amf Symbiosis On Growth Yield and Seedmentioning
confidence: 95%